The contribution of fatty acids composition of soybean oil on natural and electro-optics polarization. (April 2020) - Rahmawati, A; Firdausi, K S; Sugito, H; Azzam, M; Richardina, V; Susanto, Q M B
Abstract: A study of light polarization as a new alternative test of cooking oil quality today provides an advantage in biophysics and other fields. In this research, we determined the relation between polarization and fatty acids composition of soybean oil. The light source was a green pointer laser with λ = 532 nm, and the electro-optics polarization was produced through high DC voltage 0-9 kV across the sample. The results show that natural polarization and electro-optics polarization give different physical meanings in relation to oil fatty acid composition. The natural polarization informed that the increasing polarization was caused by increasing poly-unsaturated acids and saturated acids in asymmetric triglyceride molecules. It was accompanied by the decreasing polarization due to the increasing monounsaturated in symmetric triglyceride molecules. While the electro-optics polarization described that all fatty acids contribute to the increasing polarization due to increased induced dipole from all acids.